Realita Sosial di Sekitar Wacana Kasus Kekerasan Seksual Akun @Tt_Guillaume - Sulistiyawati, Rahmalia Intan; Firmonasari, Aprillia (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
The problem of sexual violence has become a sensitive issue that has attracted the attention of various groups of people. In addition, this action classifies as a criminal act that causes physical and psychological harm. Sexual violence happens not only to women's groups but also to subordinated minority groups in society, such as the LGBTQ+ group. In early 2021, to be precise, in France, a student and student activist experienced sexual aggression by a politician from one of the dominant political parties there. He tried to seek justice by making testimony through his Twitter account. Unexpectedly, his testimony uttered various reactions related to the social reality of society. This article aims to explore and analyze the social context and speech response patterns that represent that context. Multiple stories of netizens' responses to testimonies of sexual violence uploaded by the @TT_Guillaume account that occurred in 2018 became the object of the study of this article. In writing the article, the method used is reading all the responses in the reply section, recording all the answers found. Moreover, the next step is classifying dan analyzing the data found, which is associated with Norman Fairclough's critical discourse analysis theory. The research discovers that the social context of Guillaume's utterances was related to sexual violence in institutions in France and influenced the presence of other testimonies. In addition, patterns that represent these social conditions were also found